Safety & efficacy of intrauterine gene therapy in a clinically relevant non-human primate model - Citra Nurfarah Zaini Mattar (2019)
British Society for Gene and Cell Therapy Annual Conference and Joint UK Regenerative Medicine Platform Meeting